2017
DOI: 10.1002/jclp.22473
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Army National Guard Versus Active Duty Soldier Status and Perceived Burdensomeness, Thwarted Belongingness, and Acquired Capability

Abstract: These findings support the notion that National Guard and active duty soldiers differ on perceived burdensomeness and thwarted belongingness. Additional research investigating sources of perceived burdensomeness and thwarted belongingness among guardsmen is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We converted the measures into a common metric and controlled for the version in the substantive analyses, but determining the superiority of one set over the other was beyond the scope of our investigation. In terms of sampling, active duty military couples comprised 90% of our sample, which did not permit a reasonable test of whether National Guard and reserve component military couples have unique experiences (e.g., Podlogar et al, ). Men comprised 99% of our sample of returning service members, and women comprised 99% of our sample of at‐home partners, which precluded conclusions about deployment versus gender.…”
Section: Discussionmentioning
confidence: 99%
“…We converted the measures into a common metric and controlled for the version in the substantive analyses, but determining the superiority of one set over the other was beyond the scope of our investigation. In terms of sampling, active duty military couples comprised 90% of our sample, which did not permit a reasonable test of whether National Guard and reserve component military couples have unique experiences (e.g., Podlogar et al, ). Men comprised 99% of our sample of returning service members, and women comprised 99% of our sample of at‐home partners, which precluded conclusions about deployment versus gender.…”
Section: Discussionmentioning
confidence: 99%
“…The sample also primarily focused on the high risk and understudied U.S. Army National Guard. These individuals have the highest rate of suicide within the military and are especially prone to feelings of thwarted belongingness and perceived burdensomeness as compared to active duty military (Podlogar et al., ). Finally, this study is unique in examining a mechanism through which PTSD facilitates suicide ideation and action.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that in a military sample (91.8% National Guard), hostility was associated with perceived burdensomeness, but only at mean and high levels of negative urgency. Previous research utilizing a U.S. Army National Guard sample indicates that these individuals are especially prone to feelings of thwarted belongingness and perceived burdensomeness due to their roles as both civilian and military members (Podlogar et al, ). These findings provide support for theories suggesting individual's temperament plays a vital role in their perception of the quality of their relationships with others.…”
Section: Discussionmentioning
confidence: 99%